The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4103/0019-5359.99597
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions to antiretroviral therapy in aids patients at a tertiary care hospital in India: A prospective observational study

Abstract: Myriad ADRs are associated with ART which leads to poor patient compliance. With the increasing access to ART in India, it is prudent that antiretroviral drugs are used judicially with regular monitoring of ADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…Our findings indicated a high proportion of patients (89.8%) reported at least one adverse drug reactions because of antiretroviral therapy since they began ART. This finding is closely consistent with works of other studies that showed a high proportion of patients on ART reported at least one ADR to be as high as 86%-94% of the patients [8,11,14,19]. Almost, all these studies used a similar study design.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings indicated a high proportion of patients (89.8%) reported at least one adverse drug reactions because of antiretroviral therapy since they began ART. This finding is closely consistent with works of other studies that showed a high proportion of patients on ART reported at least one ADR to be as high as 86%-94% of the patients [8,11,14,19]. Almost, all these studies used a similar study design.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous studies, gastrointestinal complaints were the reactions most commonly encountered [4,8,11]. In a Brazilian study of 406 patients, the most frequently reported adverse drug reaction was nausea where the occurrence was as high as 51.2% [8].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations